APPLICATION OF SELF-POTENTIAL METHOD TO ESTIMATE SALTWATER DISTRIBUTION AROUND BRINE WELL IN MANIS RAYA VILLAGE, SINTANG REGENCY - Rosno, Medi; Muhardi, Muhardi; Zulian, Zulian (JOURNAL ONLINE OF PHYSICS, 2024)
This research aims to estimate saltwater distribution around the  of Manis Raya Village, Sintang Regency. This research uses the self-potential method by a fixed base configuration. Measurements in the field applied eight tracks that have a length of 120 m each with a distance of 5 m for each track and 5 m for each porous spot. The distribution of saltwater around the brine well was obtained by interpolation using the kriging method. The measurement results show that the self-potential at the research location is -99.38 mV to 158.32 mV. The interpretation results show that the area of accumulated saltwater distribution is negative, located on the east, southeast, south and west sides of the . The low self-potential of saltwater is likely due to the accumulation of ions in the area. The saltwater distribution zone is suspected to be about 48 m to the southeast of the brine well.